CLOUD REPOSITORIES AND THEIR ROLE IN ENRICHING ARAB INTELLECTUAL PRODUCTION - Alsereihy, Duha Hassan (Acta Scientiae et Intellectus, 2024)
Access to knowledge is an essential requirement for all aspects of human development. The technological development of information and the bursting of data and information across the Internet have led to the emergence of the importance of cloud computing and digital repositories that work to save data and information in all its different forms using computers and networks. This rapid development not only affected the size of data and information and methods of archiving, but also led to the emergence of different types of repositories. Thus, and in view of the importance of the subject of technologies for storing large digital data, this paper aims at achieving a major goal which is to enrich the specialized Arab intellectual production within the emergence of cloud repositories and the related concepts. Moreover, the paper seeks to achieve an important sub goal that is to identify the concepts of digital library, digital repository and institutional repository and highlight their goals, advantages and challenges and the most prominent digital repository systems. This is achieved through answering the study question that deals with the knowledge of cloud repositories and related terms and how important they are to institutions and individuals. The study depends on the critical and theoretical review and analysis of intellectual production. The researcher followed the documentary review method and content analysis to follow terms such as digital library, digital repository, institutional repository and digital repository systems.